Capacity Building on Food-Crop Farming to Improve Food Production and Food Security in Central Java, Indonesia - Waridin (Asian Journal of Agriculture and Rural Development, 2013)
This paper describes the capacity of food-crop production for improving regional food security in Central Java, Indonesia. It is also identify crops which have high and prospective economic-values. The results of the study might help in formulating a proposed model to improve food crops production in supporting food security. The case study was conducted in districts which play the important roles on agriculture (rice) production in Central Java, Indonesia. These are Klaten and Magelang districts. Data were collected from farmers and officers from agriculture-related institutions. The results show that Central Java Province has the capacity on food crop (rice) production for securing food availability, distribution, and accessibility for people in the region. It has a moderate on food security for the products, and surplus of production have distributed to other regions within the country. However, other food crops still facing shortage of supply since lack of productions. It requires a commitment from government and stakeholders for improving capacity building on agricultural development.